The new Reform Judaism : challenges and reflections - Kaplan, Dana Evan (The Jewish Publication Society, 2013)
This is the book that American Jews and particularly American Reform Jews have been waiting for: a clear and informed call for further reform in the Reform movement. In light of profound demographic, social, and technological developments, it has become increasingly clear that the Reform movement will need to make major changes to meet the needs of a quickly evolving American Jewish population. Younger Americans in particular differ from previous generations in how they relate to organized religion, often preferring to network through virtual groups or gather in informal settings.